Pengaruh Teknologi Informasi dan Budaya dalam Organisasi terhadap Laporan Keuangan Akuntansi di Era Pandemi Tahun 2021 - Sopiyana, Muhammad; Budiman, Septian Arif; Mulyani, Nani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to find out how developments in information technology have brought significant changes to the field of accounting in financial reports. This influence also adapts and influences human culture in the social system in the current pandemic era. The research method uses a quantitative approach with panel data regression analysis techniques. Research data was obtained from the financial reports of 7 food companies listed on the Indonesian stock exchange, which were determined using a purposive sampling technique. The partial research results show that the influence of information technology and culture on accounting financial reports has a positive or negative effect in the current pandemic era. However, simultaneously information technology and organizational culture factors make a large contribution to the quality of accounting financial reports with a percentage of 63,02%.